ANALISIS METODE MUHAMMAD IDRIS AL-MARBAWI DALAM KITAB MUKHTASAR SHAHIH AT-TIRMIZI WA SYARHUHU BI LUGHAH AL-JAWI AL-MALAYU AL-MUSAMMA BAHR AL-MADZI - Fadhilah Is (UIN Sumatera Utara Medan, 2021)
The development of hadith studies in Southeast Asia in the 20th century was divided into two characteristics, namely traditional and modern. The style of traditional hadith studies is marked by the many translations of hadith books from Arabic. Among the hadith figures from Malay who have produced many and varied written works are Shaykh Muhammad Idris al-Marbawi from Malaisya. His monumental work in the field of hadith is the book Bahr al-Mazi. This book in Malay contains syarh hadith, there are 2781 hadith from the book al-Jami'at-Tirmizi, consisting of 22 volumes with 5068 pages, 8282 issues regarding the subject of hadith and information on the identity of the narrators.